Antifibrillatory effects of renal denervation on ventricular fibrillation in a canine model of pacing‐induced heart failure. Issue 1 (28th November 2017) - Luo, Qingzhi; Jin, Qi; Zhang, Ning; Huang, Shangwei; Han, Yanxin; Lin, Changjian; Ling, Tianyou; Chen, Kang; Pan, Wenqi; Wu, Liqun
Abstract : New Findings: What is the central question of this study? In the present study, we investigated the effects of renal denervation on the vulnerability to ventricular fibrillation and the ventricular electrical properties in a rapid pacing‐induced heart failure canine model. What is the main finding and its importance? Renal denervation significantly attenuated the process of heart failure and improved left ventricular systolic dysfunction, stabilized ventricular electrophysiological properties and decreased the vulnerability of the heart to ventricular fibrillation during heart failure. Thus, renal denervation can attenuate ventricular electrical remodelling and exert a potential antifibrillatory action in a pacing‐induced heart failure canine model. In this study, we investigated the effects of renal denervation (RDN) on the vulnerability to ventricular fibrillation (VF) and the ventricular electrical properties in a canine model of pacing‐induced heart failure (HF). Eighteen beagles were divided into the following three groups: control ( n  = 6), HF ( n  = 6) and HF+RDN ( n  = 6). Heart failure was induced by rapid right ventricular pacing. Renal denervation was performed simultaneously with the pacemaker implantation in the HF+RDN group. A 64‐unipolar basket catheter was used to perform global endocardial mapping of the left ventricle. The restitution properties and dispersion of refractoriness were estimated from the activation recovery intervals (ARIs) by a pacing protocol. The VF threshold (VFT) was defined as the maximal pacing cycle length required to induce VF using a specific pacing protocol. The defibrillation threshold (DFT) was measured by an up–down algorithm. Renal denervation partly restored left ventricular systolic function and attenuated the process of HF. Compared with the control group, the VFT in the HF group was decreased by 27% (106 ± 8.0 versus 135 ± 10 ms, P  < 0.01). However, RDN increased the VFT by 13% (135 ± 10 versus 118 ± 7.5 ms, P  < 0.05) and decreased the DFT by 27% (30 ± 6.3 versus 21.8 ± 4.7 J, P  < 0.05) in the treated hearts compared with the failing hearts. Renal denervation significantly flattened the ventricular ARI restitution curve by 15% (1.48 ± 0.2 versus 1.26 ± 0.11, P  < 0.05) and decreased the dispersion of ARI by 25% (0.08 ± 0.02 versus 0.06 ± 0.01, P  < 0.01) in the treated group compared with the HF group. The findings of this study suggest that RDN can attenuate ventricular electrical remodelling and exert a potential antifibrillatory action on VF in a canine model of pacing‐induced HF. Abstract :